Emerging Food Tourism in India : Are Foodscape Destinations Strategically Branded? A Perspective - Shankar R, Sabari (Prabandhan: Indian Journal of Management, 2022)
Food tourism is becoming very popular in India as the country possesses a greater linkage of food with culture, tradition, heritage, health, and so on. Tourists across the globe prefer India as their choice for satisfying their food motives. This form of tourism is highly profitable and viable to promote the other tourism types. Though food destinations are branded effectively , a strategic approach of inculcating the critical aspects of sustainability , such as regeneration, rediscovery , and circular economy , in the branding process is unseen. This perspective note indicates the relevance and importance of including those critical factors in strategic food destination branding process for a sustainable future. The perspective evoked in-depth and doable thoughts of blending the sustainability elements in branding the food destinations based on the self-reflection inferences, research readings, and interactions with the destination management organizations and marketers.